consider the function f(x) = 2x - 1

what is the output if the input is x = -3

1 answer

To find the output of the function when the input is x = -3, we simply substitute -3 in place of x in the function and solve:

f(x) = 2x - 1
f(-3) = 2(-3) - 1
f(-3) = -6 - 1
f(-3) = -7

Thus, the output of the function f(x) = 2x - 1 when the input is x = -3 is -7.
Similar Questions
  1. Write a function rule for the statement.1. The output is half of the input. 2. The output is three less than the input. 3. The
    1. answers icon 1 answer
    1. answers icon 48 answers
  2. identify the function rule from the values in the table.input | output -1 | -2 0 | -1 1 | 0 2 | 0 A. output equals input times
    1. answers icon 53 answers
    1. answers icon 6 answers
more similar questions